ASSESSMENT OF RELATIONSHIPS AND VARIABILITY OF MORPHOPHYSIOLOGICAL CHARACTERS IN BREAD WHEAT (TRITICUM AESTIVUM L.) UNDER DROUGHT STRESS AND IRRIGATED CONDITIONS - SINGH, AKHILESH KUMAR; SINGH, SATISH KUMAR; GARG, HIMANSHU SHEKHAR; KUMAR, RAJESH; CHOUDHARY, RAKESH (The Bioscan, 2014)
Thirty nine genotypes of bread wheat were evaluated under two conditions (drought stress and irrigated) to study the variability, correlation and path coefficient analysis based on sixteen morpho-physiological traits viz, days to fifty per cent flowering, days to maturity, spike length, plant height, chlorophyll content, flag leaf area, canopy temperature, relative water content (RWC), number of tillers per plant, number of grains per spike, grain yield per plant, 1000 grain weight, harvest index (HI), drought susceptibility index (DSI), germination percentage and seed vigour index (SVI). Analysis of variance revealed highly significant variation among the genotypes for all the characters under studied in both conditions. The variability study indicated high to moderate phenotypic and genotypic coefficient of variation accompanied by high heritability and genetic advance as per cent of mean for traits like number of tillers per plant, grain yield per plant, 1000 grain weight, flag leaf area, chlorophyll content and harvest index indicating their importance in selection for yield improvement under both conditions. Correlation studies indicated that number of tillers per plant, 1000 grain weight, harvest index, number of grains per spike, flag leaf area, chlorophyll content, relative water content and seed vigour index showed significant positive association with grain yield per plant as well as among themselves at phenotypic and genotypic level under both environments. However, grain yield per plant showed negative significant correlation with canopy temperature in both conditions. Further, path coefficient analysis revealed that under rainfed condition highest positive direct effect was exhibited by number of tillers per plant and flag leaf area, while under irrigated condition number of grains per spike, 1000 grain weight and number of tillers per plant had highest positive direct effect. Thus, these traits may be used as selection criteria for respective environments for further improvement. The highest negative direct effect was showed by canopy temperature on grain yield under both conditions (drought stress and irrigated).